The Electric Energy Sector of Kazakhstan: State and Vision for the Country Taking into Account the International Trends - Dyussembekova, Gulsara; Bayandina, Gulmira; Zakirova, Dilnara; Sartova, Rysty; Kalmenova, Marzhan (International Journal of Energy Economics and Policy, 2019)
The main objective of this paper is the study of the modern state of the electric energy sector of the Republic of Kazakhstan, as well as the determination of some promising directions of the country in view of the global trend of the electric energy sector. The desk study, trend analysis, and literature review were used as the methods of the research. The conducted research allowed concluding that many factors had significant influence on a rapid change of the global energy sector and the way energy was produced and consumed as well (including the climate change, development of new sources of energy, application of innovative technologies). Nowadays, the electric energy sector of the Republic of Kazakhstan is facing a lot of intrinsic factors (including the need to modernize infrastructure), as well as the changes in global markets which require long-term planning and the environment for attracting new investments. It is necessary to take into account the global energy environment during the development of a growth strategy, including some changes in the dynamics and organization of the world production and demand in energy, development of renewable energy resources, and implementation of "smart" networks. Keywords: electric energy sector, fuel and energy complex, alternative sources, renewables, energy infrastructure. JEL Classifications: Q20, Q42 DOI: https://doi.org/10.32479/ijeep.7741